A new site from the Spanish Middle Pleistocene with cold-resistant faunal elements: La Parte (Asturias, Spain) - Álvarez Lao, Diego; García García, Nuria (Quaternary International, 2006)
The La Parte (Asturias) northern Spain site contains a cold-adapted mammal faunal assemblage that corresponds to a level radiometrically dated to a minimum age of 150 ka. It represents the most ancient site with cold resistant fauna in the Iberian Peninsula. Among the species recorded in La Parte, Coelodonta antiquitatis and Rangifer tarandus represent the typical cold-adapted large mammal association. The presence of the woolly rhino at La Parte provides relevant environmental information about the Mammoth Steppe. This species was not as abundant in the Middle Pleistocene as during the Late Pleistocene, when its cold-adapted features can be studied from an evolutionary perspective. The remains attributed to R. tarandus suggest an open steppe ecosystem. The presence of Marmota sp. is also confirmed in La Parte. A first interpretation would suggest an alpine or periglacial ecosystem, but based on recent results which do not support the correlation between phylogeny and climatic tolerance for extant species of Marmota (López and Cuenca, 2002. Palaeogeography, Palaeoclimatology, Palaeoecology 186, 311), we propose the presence of this rodent suggests an open landscape with cold conditions. The rest of the taxa included in the La Parte assemblage (Crocuta crocuta, Panthera leo, Cervus elaphus, Megaloceros cf. giganteus, Bison priscus and Equus caballus) are usually associated with typical cold-adapted faunas, but they are also found in woody temperate zones so they do not characterize by themselves a cold period. The faunal association from La Parte suggests a combination of steppic and open woodland ecological conditions. Dirección General de Investigación Científica y Técnica Depto. de Geodinámica, Estratigrafía y Paleontología Fac. de Ciencias Geológicas TRUE pub